Differences in the rheological properties of esterified total, A‐type, and B‐type wheat starches and their effects on the quality of noodles. Issue 3 (14th December 2019) - Hong, Jing; Li, Chaopeng; An, Di; Liu, Chong; Li, Limin; Han, Zhong; Zeng, Xin‐An; Zheng, Xueling; Cai, Mengjie
Abstract: Total starch (TS), large A‐type starch (AS), and small B‐type starch (BS) separated from wheat flour were used to be esterified with acetic anhydride via conventional and pulsed electric field‐assisted (PEF‐assisted) methods. The rheological properties of these esterified wheat starch and their effects on the quality of noodles were studied. The RVA results showed that the two esterification methods can reduce the peak viscosity of TS, AS, and increase that of BS and it was higher as modified by the PEF‐assisted method. While the loss factor of gel expressed the opposite trend. Gel hardness of all types of starch was greatly reduced by modification, especially for PEF‐assisted esterification. After adding modified starches to the noodle‐making flour, all the esterified starches can improve the color of noodles and increase the water absorption rate. Compared with noodles adding native BS, the stretching distance of noodles was added by 12 mm after being added PEF‐assisted esterified BS. Practical applications: This study explored the effects of esterification on total starch (TS), large size of A‐type starch (AS), and small size of B‐type starch (BS) as well as the modified starches applied on noodles. Adding pulsed electric field (PEF)‐assisted esterified starch was beneficial to improve the hardness of noodles and increase the stretching distance especially for that of adding PEF‐assisted BS. These results provide a technical reference that PEF‐assisted esterified starch, which can be considered as a food additive improver, has greater feasibility and effectiveness than conventionally esterified starch and it brings new light on the role of PEF technology in the texture and quality of cereal products.